Automatic Voltage Generation Control for Two Area Power System Based on Particle Swarm Optimization - Ali M. Ali; M.A. Ebrahim; M.A. Moustafa Hassan (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
This article presentes a PID controller for two area power system equipped with both automatic generation control and automatic voltage regulator loops. The research has been done to control two area power systems with PSO optimized self-tuning PID controller. The comparison between different controllers and the suggested PSO based controller illustrates that the proposed controller can generate the best dynamic response for a step load change. For this purpose, MATLAB-Simulink software is used. The obtained results are promising.